2016
DOI: 10.1038/srep37621
|View full text |Cite
|
Sign up to set email alerts
|

No evidence of NRAS mutation in squamous cell anal carcinoma (SCAC)

Abstract: Epidermal growth factor receptor (EGFR) is usually expressed in squamous cell anal carcinoma (SCAC) and anti-EGFR agents could represent a valid treatment strategy, also considering that KRAS and BRAF mutations are rare events in this type of cancer. However, no data are available on NRAS status in SCAC. In this study we analyzed NRAS status (exons 2–4) by Pyrosequencing in a case series of 50 SCAC patients previously characterized in our laboratory for KRAS, BRAF, PIK3CA mutations and HPV and HIV infections. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Genotyping analysis of 5 single nucleotide polymorphisms (SNPs) ( VEGF −2578C>A, −1498C>T, −1154G>A, −634C>G, +936C>T) for VEGF and 2 SNPs ( eNOS −786T>C, +894G>T) and one variable number tandem repeat (VNTR) of 27 nucleotides for eNOS was performed on peripheral blood samples, as previously reported [ 15 ]. Exons 2, 3 and 4 of KRAS and NRAS and exon 15 of BRAF genes were also analyzed by pyrosequencing, as previously described [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Genotyping analysis of 5 single nucleotide polymorphisms (SNPs) ( VEGF −2578C>A, −1498C>T, −1154G>A, −634C>G, +936C>T) for VEGF and 2 SNPs ( eNOS −786T>C, +894G>T) and one variable number tandem repeat (VNTR) of 27 nucleotides for eNOS was performed on peripheral blood samples, as previously reported [ 15 ]. Exons 2, 3 and 4 of KRAS and NRAS and exon 15 of BRAF genes were also analyzed by pyrosequencing, as previously described [ 27 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, cetuximab may be an effective treatment for anal squamous cell carcinoma because EGFR is overexpressed in many cases, while KRAS, NRAS, and BRAF mutations are not observed in most cases [ 14 , 40 42 ]. Rogers et al reported that EGFR antibodies were used in second- and third-line treatments and disease control was possible for 59% of the patients [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor receptor (EGFR) is overexpressed in about 90% of SCAC, whereas KRAS and NRAS mutations are rare (Capelli et al, 2016;Casadei Gardini et al, 2014;Zampino et al, 2009;Cacheux et al, 2016). PIK3CA is mutated in 20% of patients (Capelli et al, 2016). These observations provide a theoretical rationale for integrating anti-EGFR agents into standard treatment for SCAC.…”
Section: Role Of Anti-egfr Therapy In the Treatment Of Scacmentioning
confidence: 99%
“…Immunosuppression is a risk factor for SCAC development (Nelson, 2017) and predisposes the anal epithelium to human papillomavirus (HPV) infection and its persistence. Affecting around 95% of patients with metastatic SCAC, the virus integrates into the host cell DNA and promotes oncogenesis (Capelli et al, 2016). It has been demonstrated that HPV increases the risk of cancer of the head and neck, uterine cervix, penis and vulva (Faivre et al, 1999;Jaiyesimi and Cisplatin, 1993).…”
Section: Role Of Immunotherapy In the Treatment Of Metastatic Scacmentioning
confidence: 99%
See 1 more Smart Citation